Analisis Korelasi antara Intensitas Mengakses Media Sosial dengan Persepsi tentang Puisi “Doa Yang Ditukar” pada Anggota Mahasiswa Nahdlatul Ulama (KMNU) UIN Sunan Kalijaga Yogyakarta - Faiz, Achmad Zaky (Faculty of Da'wa and Communications Sciences, 2022)
This article aims to determine the relationship between the intensity of access to social media with students' perceptions of the Poetry